Pengembangan Ekowisata Berbasis Konservasi Lingkungan dan Ekonomi Sirkular - Zainal Abidin; Mashur Razak; Ahmad Firman; Muhammad Idris; Fitriani Latief; Pierre Johnson (Ilin Institute, 2026)
Sustainable tourism development is an important strategy for addressing environmental challenges in tourist destinations. This community service activity aims to develop a circular economy–based ecotourism model through strengthening community waste bank institutions in the Rammang-Rammang tourism area. The main problems faced by partners are suboptimal waste management and the limited integration of tourism activities with environmental conservation. The implementation method uses a Participatory Action Research approach which includes socialization, waste management training, and institutional mentoring. The activity was carried out in November 2025 involving international speakers and local educators. The results show an increase in community understanding of zero waste tourism, the formation of community commitment to waste bank management, and practical training in the use of composters for organic waste. This program is expected to support community economic independence through recycled products while maintaining the sustainability of the Rammang-Rammang karst ecosystem.